Kearifan Lokal Sukur Laut Dalam Pengelolaan Sumber Daya Laut di Pesisir Pantai Pamayang Kecamatan Cipatujah - Mohamad Mardatillah; Erni Mulyanie (Kilau Publishing, 2024)
The local wisdom of the Sea Gratitude tradition is an activity carried out by the community around the Pamayangsari coast. This activity has traditional values that can be studied, the tradition of the Sea Gratitude party is held once a year and is carried out from generation to generation. The tradition of the Sea Gratitude party is a ritual activity as a form of expression of gratitude of the fishermen for the sea products or fish catches that the fishermen obtained during the past year. The background of this writer is to examine how the process of sea gratitude rituals and the benefits between the Sea Gratitude party and the marine environment, especially the marine ecosystem. The purpose of this research is to find out how the process of the sea gratitude tradition is carried out and the benefits for the marine environment or marine ecosystem on Pamayangsari Cipatujah beach. The research method used is literature study. Literature study is a series of activities related to how to collect library data, read and record, and manage research data objectively, systematically, analytically, and critically about the local wisdom of the sea gratitude tradition at Pamayangsari Cipatujah Tasikmalaya beach. Through this research, it is hoped that it can provide benefits and can stabilize the values contained therein. Keywords: Local Wisdom, Sea Gratitude Tradition, Environment